The Promise of Long-Acting Antiretroviral Therapies: From Need to Manufacture. Issue 7 (July 2019) - Gendelman, Howard E.; McMillan, JoEllyn; Bade, Aditya N.; Edagwa, Benson; Kevadiya, Bhavesh D.
Abstract : Antiretroviral therapy has transformed human immunodeficiency virus infections from certain death to a manageable chronic disease. Achieving strict adherence to drug regimens that limit toxicities and viral resistance is an achievable goal. Success is defined by halting viral transmission and by continuous viral restriction. A step towards improving treatment outcomes is in long-acting antiretrovirals. While early results remain encouraging there remain opportunities for improvement. These rest, in part, on the required large drug dosing volumes, local injection-site reactions, and frequency of injections. Thus, implantable devices and long-acting parenteral prodrugs have emerged which may provide more effective clinical outcomes. The recent successes in transforming native antiretrovirals into lipophilic and hydrophobic prodrugs stabilized into biocompatible surfactants can positively affect both. Formulating antiretroviral prodrugs demonstrates improvements in cell and tissue targeting, in drug-dosing intervals, and in the administered volumes of nanosuspensions. As such, the newer formulations also hold the potential to suppress viral loads beyond more conventional therapies with the ultimate goal of HIV-1 elimination when combined with other modalities. Highlights: Long-acting parenteral antiretroviral drugs (antiretrovirals, ARVs) can improve regimen adherence, limit toxicities, and reduce viral resistance. Prodrug ARV formulations increase the apparent half-life and facilitate drug entry and retention into infectious reservoirs. Long-acting slow effective release antiretroviral therapies (LASER ART) are hydrophobic lipophilic ARV nanocrystals with a defined 200 to 400 nm size. Controlled prodrug release and slowed hydrolysis can prolong half-life, improve pharmacokinetic profiles, and facilitate native ARV tissue biodistribution. LASER ART can lower viral transmission rates, improve treatment outcomes, and facilitate pre-exposure prophylaxis regimens in virus-infected or susceptible individuals. Scale-up by good laboratory and manufacturing practices facilitates LASER ART translation.